PENGEMBANGAN POCKET BOOK OF MATHEMATIC PADA SISWA BERKEBUTUHAN KHUSUS UNTUK MEMFASILITASI KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS - Devi Ariyantika; Farida Farida; Rosida Rakhmawati (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
Learning media have an important role in the learning process of students. Seeing student learning outcomes decline, indicating that students' understanding of the material is also quite low. The media that is considered appropriate and in accordance with the current conditions is the Pocket Book of Mathematic learning media. Students in general always have their own way of learning this knowledge, but in this case people with disabilities are mentally retarded children, children who find it difficult to understand mathematical concepts so many still need help in their understanding. The purpose of this study is to: (1) Know how the feasibility of learning media in the form of pocket book of mathematic for mentally retarded children. (2) Knowing how the response from teachers and students regarding learning media in the form of pocket book of mathematic developed. (3) knowing the effectiveness of pocket book of mathematic media that has been produced when applied in learning which will be seen from the results of calculations by media experts and students. This study uses the ADDIE research method with 5 stages of development, namely (1) Analysis (2) planning (3) Product Development (4) Application (5) Evaluation, with data collection techniques using interviews and questionnaires (questionnaires), data analysis techniques used namely qualitative descriptive statistics. The results of this study are a mathematical learning media in the form of a pocket book of mathematic for children with special needs (ABK) to facilitate students' conceptual comprehension skills for SLB Dharma Bhakti Dharma Pertiwi Bandar Lampung students. The feasibility of the media was declared valid by material experts and media experts, and received a